Accomplishments, shortcomings and challenges : evaluation of the Special Court for Sierra Leone - Fernandez, Lovell (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.